1997
DOI: 10.4315/0362-028x-60.7.761
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Microbial Quality of Chicken as Affected by Irradiation and Postirradiation Storage at 4.0°C

Abstract: Chickens were subjected to gamma irradiation doses of 2.5, 5.0,7.5, and 10.0 kGy using a semi-commercial gamma irradiation facility. The irradiated and unirradiated (control) chickens were stored at 4.0°C, and samples were drawn at day 0 and at 3-day intervals up to 21 days for sensory and microbiological analyses. All irradiation doses (2.5 to 10.0 kGy) had little effect on the sensory acceptability (appearance, odor, texture, taste) of both raw and cooked chicken (breast and thigh). Irradiation extended the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 0 publications
1
38
1
3
Order By: Relevance
“…Vacuum packaging combined with irradiation at 3.0 kGy resulted in extending the shelf life to 12 days, which was more than double in comparison with the unirradiated air-packed samples that remained good for five days only. These findings were consistent with those obtained by Abu-Tarboush et al (1997) who reported that irradiation of refrigerated chicken meat with 2.5 kGy led to a 12-day shelf life.Similar results were observed by Grandison and Jennings (1993), who reported that air-packed unirradiated samples of ground chicken meat deteriorated in two days of storage, while the treatment with 3.1 kGy significantly increased the shelf life of the samples. Chouliara et al (2008) also found an extension in the shelf life of fresh poultry meat treated with 2.0 and 4.0 Gy.…”
Section: Shelf-life Extensionsupporting
confidence: 93%
See 1 more Smart Citation
“…Vacuum packaging combined with irradiation at 3.0 kGy resulted in extending the shelf life to 12 days, which was more than double in comparison with the unirradiated air-packed samples that remained good for five days only. These findings were consistent with those obtained by Abu-Tarboush et al (1997) who reported that irradiation of refrigerated chicken meat with 2.5 kGy led to a 12-day shelf life.Similar results were observed by Grandison and Jennings (1993), who reported that air-packed unirradiated samples of ground chicken meat deteriorated in two days of storage, while the treatment with 3.1 kGy significantly increased the shelf life of the samples. Chouliara et al (2008) also found an extension in the shelf life of fresh poultry meat treated with 2.0 and 4.0 Gy.…”
Section: Shelf-life Extensionsupporting
confidence: 93%
“…According to the data that group was eliminated from the chicken fillets irradiated to 3.0 kGy, and had difficulty to start growth after irradiation with 2.0 kGy. Abu-Tarboush et al (1997) also found that irradiation with 2.5 kGy and storage at 4°C for 21 days was sufficient to eliminate total coliforms in chicken meat. In another experiment, gamma irradiation of chicken with 1 and 1.8 kGy was sufficient to eliminate total coliforms (Lewis et al, 2002).…”
Section: Coliformsmentioning
confidence: 84%
“…Our previous study (Fallah et al, 2008) showed that irradiation (1.5 and 3 kGy) had no significant effects on sensory attributes of fried burgers prepared from camel meat. Abu-Tarboush et al (1997) concluded that irradiation (2.5-10 kGy) had little effect on the sensory acceptability (appearance, odor, taste and texture) on both raw and cooked chicken meat.…”
Section: Sensory Evaluationmentioning
confidence: 97%
“…As amostras tratadas com 1,5 e 3,0kGy atingiram valores próximos aos encontrados nas amostras-controle somente no 22 e 29 o dias, respectivamente. Esse dado discorda dos trabalhos publicados por ABU-TARBOUSH et al [1] e KAZANAS et al [20] que relataram pouca influência no desenvolvimento da população microbiana com o aumento da dose de irradiação. Uma diminuição significativa das bactérias mesófilas aeróbias foi observado para amostras irradiadas com 7,0kGy, apresentando contagens inferiores a 7log UFC/g mesmo após 39 dias de estocagem.…”
Section: Rsd = Desvio Padrão Relativounclassified